Iron-based magnetic core with constant magnetic conductivity as well as preparation method and application of iron-based magnetic core
By performing force-field heat treatment and magnetic field heat treatment on the iron-based amorphous magnetic core, the structure of grains and magnetic domain walls is regulated, and the problem of unstable magnetic permeability at high frequency is solved, and the iron-based magnetic core is achieved at 1-100KHz Constancy and stability of magnetic permeability at frequency.
Patent Information
- Application Number
- CN202411588238.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-07
AI Technical Summary
The prior art is difficult to maintain the permeability of the iron-based magnetic core within the frequency range of 1-100KHz in the range of 15000-35000, resulting in a significant reduction in the permeability of the magnetic core at high frequencies, which cannot meet the application needs of stable magnetic permeability.
By sequentially performing force field heat treatment and magnetic field heat treatment at specific temperatures, the grain size, state, magnetic anisotropy and hysteresis loop shape are controlled to ensure that the core has a constant at a frequency of 1-100KHz. Permeability.
The stability and constant of the permeability of the iron-based magnetic core at the frequency of 1-100KHz is achieved, and the permeability is maintained within the range of 15000-35000, which widens the application scenarios of the iron-based magnetic core.
Smart Images

Figure CN119400582A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of magnetic materials, and in particular relates to an iron-based magnetic core with constant magnetic permeability and a preparation method and application thereof. Background Art
[0002] Iron-based amorphous / nanocrystalline soft magnetic alloys are usually made of amorphous strips by high-speed copper roller rapid cooling process from master alloys, and the amorphous strips are wound into amorphous magnetic cores. Amorphous magnetic cores generally need to undergo appropriate heat treatment processes to finely control the microstructure of the alloy, that is, a single magnetic α-Fe phase is precipitated on the amorphous matrix to transform into a two-phase coexistence structure of amorphous and nanocrystalline to form a nanocrystalline magnetic core. This special two-phase nanostructure is also the main reason why the nanocrystalline magnetic core exhibits excellent comprehensive soft magnetic properties. Therefore, the heat treatment process of the magnetic core plays a decisive role in obtaining high-performance iron-based magnetic cores. However, the heat treatment process in the prior art often produces a magnetic core with high magnetic permeability and a significant decrease with the increase of frequency. The magnetic permeability is unstable, which makes the magnetic core unable to be used in equipment that requires stable magnetic permeability, especially it is impossible to obtain an iron-based magnetic core with an effective magnetic permeability of 15000-35000 at 1-100KHz, which limits its application.
[0003] Therefore, it is urgent to develop a heat treatment process for an iron-based magnetic core to achieve an iron-based magnetic core with a magnetic permeability in the range of 15000-35000 at 1-100 KHz. Summary of the invention
[0004] In view of the problem in the prior art that it is difficult to obtain an iron-based magnetic core with a magnetic permeability in the range of 15000-35000 at 1-100 KHz, the present invention provides an iron-based magnetic core with constant magnetic permeability and a preparation method and application thereof.
[0005] To achieve the above purpose, the following technical solutions are specifically included:
[0006] A method for preparing an iron-based magnetic core comprises the following steps:
[0007] (1) heating the iron-based amorphous magnetic core to a preset temperature and pressurizing it to a preset pressure, and then cooling it to below 200° C. and releasing the pressure to obtain a pre-burned magnetic core; the preset temperature is 530-650° C., and the preset pressure is greater than atmospheric pressure;
[0008] (2) The pre-burned magnetic core is subjected to a magnetic field heat treatment, and after cooling, an iron-based magnetic core is obtained, wherein the temperature of the magnetic field heat treatment is 435-550°C.
[0009] In the method of the present invention, by subjecting the iron-based amorphous magnetic core to force field heat treatment and magnetic field heat treatment at specific temperatures in sequence, the iron-based magnetic core has an effective magnetic permeability of 15000-35000 at a frequency of 1-100kHz, thereby broadening the application scenarios of the iron-based magnetic core.
[0010] Under the force field heat treatment, on the one hand, the pressure promotes the precipitation of nano-crystal grains but at the same time inhibits the rapid growth of nano-crystal grains. To a certain extent, the magnetic core is kept at a relatively low magnetic permeability and a relatively stable magnetic permeability by controlling the grain size; on the other hand, the existence of the pressure field can induce magnetic anisotropy inside the magnetic core, increase the domain wall energy, and the high domain wall energy prevents the movement of the domain wall. To a certain extent, the magnetic permeability of the magnetic core is relatively low and the magnetic permeability is relatively stable by regulating the domain wall energy. The actual effect of the magnetic field heat treatment is to induce the oriented growth of grains, that is, to promote the orientation of nano-crystal grains along the direction of magnetic field application, thereby inducing magnetic anisotropy and regulating the shape of the hysteresis loop. The force field heat treatment and the magnetic field heat treatment are mutually coordinated. It is necessary to regulate the oriented growth of grains by the magnetic field heat treatment on the basis of regulating the grains and the magnetic domain wall energy by the force field heat treatment. The present invention regulates the grain size, state, magnetic anisotropy, the shape of the hysteresis loop, etc. by changing the heat treatment process to obtain a magnetic core with stable magnetic permeability at 1-100KHz. In addition, the inventors of the present invention found out through experiments that when the temperatures of force field heat treatment and magnetic field heat treatment are 530-650℃ and 435-550℃ respectively, the magnetic permeability of the magnetic core maintains high stability at 1-100KHz. A slight deviation from the above two heat treatment temperature ranges may cause abnormal grain growth, resulting in a significant increase in the rate of change of magnetic permeability, and the effect of keeping the magnetic permeability stable or constant cannot be achieved.
[0011] Preferably, in step (1), the preset pressure is 100-200 MPa.
[0012] The temperature of the force field heat treatment gradually increases, which can further increase the magnetic anisotropy induced inside the magnetic core, increase the domain wall energy, further adjust the magnetic permeability of the magnetic core, and make the stability of the magnetic permeability better; however, if the pressure is too high, the energy consumption will increase, the equipment requirements will be higher, and there may be certain safety hazards. Therefore, the present invention selects the above-mentioned pressure range, which can be more in line with actual working conditions while ensuring the magnetic properties of the magnetic core.
[0013] Preferably, in step (1), the iron-based amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%, Mo 0-10%, V 0-10%.
[0014] Further preferably, the iron-based amorphous magnetic core comprises Fe 73.5 Si 13.5 B 9 Cu 1 Nb 3 , Fe 63.5 Ni 10 Si 15.5 B 7 Cu 1 Nb 3 , Fe 63.5 Co 5 Ni 5 Si 15.5 B 7 Cu 1 Nb 3 , Fe 68.5 Co 5 Si 15.5 B 7 Cu 1 Nb 3 The method of the present invention is effective for various iron-based alloys and is suitable for heat treatment of different types of amorphous magnetic cores to obtain a magnetic core with low-frequency constant magnetic permeability.
[0015] Preferably, in step (1), the heating rate when the iron-based amorphous magnetic core is heated to a preset temperature is 5-30° C. / min.
[0016] Preferably, in step (1), the cooling rate is 50-1000° C. / min.
[0017] Further preferably, in step (1), the cooling rate is 100-500°C / min.
[0018] The method of the present invention can select a heating rate of 5-30°C / min during heating and a cooling rate of 50-1000°C / min during cooling. Compared with conventional heat treatment processes, the above-mentioned heating / cooling rate ranges belong to the situation of rapid heating and rapid cooling, which can shorten the time that the magnetic core stays at high temperature, avoid excessive growth of grains in the magnetic core, and make the magnetic permeability of the magnetic core more stable.
[0019] Preferably, the pressurization method includes at least one of pressurization by inert gas pressure and pressurization by mold extrusion.
[0020] Preferably, the inert gas includes at least one of argon and nitrogen.
[0021] Preferably, the magnetic field intensity of the magnetic field heat treatment is 800-3000 Gs.
[0022] Preferably, the iron-based amorphous core in step (1) is formed by winding an iron-based amorphous strip, and the magnetic field direction of the magnetic field heat treatment in step (2) is parallel to the width direction of the iron-based amorphous strip.
[0023] Preferably, in step (2), the time of the magnetic field heat treatment is 20-120 min.
[0024] If the temperature and time of magnetic field heat treatment are too high, the grain size in the magnetic core will be too large. Although a high magnetic permeability stability can be maintained, the magnetic permeability of the magnetic core will be significantly increased. Therefore, when the magnetic field heat treatment time is 20-120 minutes, the magnetic permeability and stability of the magnetic core are more in line with the requirements.
[0025] Preferably, in step (2), the cooling is natural cooling. Preferably, the magnetic permeability of the iron-based magnetic core is constant at a frequency of 1-100 kHz, and the magnetic permeability of the iron-based magnetic core is 15000-35000; the iron-based magnetic core contains an amorphous phase and nano-sized grains.
[0026] Further preferably, when the magnetic permeability of the iron-based magnetic core is constant, the change rate of the effective magnetic permeability of the iron-based magnetic core at a frequency of 1-100 kHz is ≤5%.
[0027] The present invention also provides an application of the iron-based magnetic core in preparing an inductor and a high-current power device.
[0028] Compared with the prior art, the present invention has the following beneficial effects: the present invention can obtain an iron-based magnetic core with constant magnetic permeability by subjecting the iron-based amorphous magnetic core to force field heat treatment and magnetic field heat treatment at specific temperatures in sequence, and the iron-based magnetic core has the characteristic of a constant magnetic permeability in the range of 15000-35000 at 1-100kHz. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is the X-ray diffraction (XRD) pattern of the homemade amorphous ribbon.
[0030] Figure 2 A comparison diagram of the magnetic domain structures between Example 1 (left) and Comparative Example 3 (right).
[0031] Figure 3 This is a physical picture of the magnetic core prepared in Example 1.
[0032] Figure 4 Graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of Examples 1 to 16.
[0033] Figure 5 This is a graph showing the relationship between the effective magnetic permeability and frequency of the iron-based nanocrystalline soft magnetic alloy cores of comparative examples 1 to 7. DETAILED DESCRIPTION
[0034] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below through specific examples. The test methods used in the examples and / or comparative examples are conventional methods unless otherwise specified; the materials, reagents, etc. used can be obtained from commercial channels unless otherwise specified.
[0035] The amorphous strips used in the following embodiments and comparative examples can be purchased from the market or prepared by conventional methods. The methods may include the following steps: (1) component proportioning; (2) master alloy smelting; and (3) obtaining the corresponding amorphous strips by strip spinning and strip winding.
[0036] Example 1
[0037] A method for preparing an iron-based magnetic core comprises the following steps:
[0038] (1) The alloy Fe in atomic percentage 73.5 Si 15.5 B 7 Cu 1 Nb 3 Amorphous strip (self-made, its XRD results are as attached Figure 1 ) is wound into an amorphous magnetic core, and then the amorphous magnetic core is placed in a furnace, evacuated, filled with inert gas argon gas, so that there is a certain pressure in the system, and heated to a force field heat treatment temperature of 580°C at a heating rate of 15°C / min, and at the same time, argon gas is continuously filled to pressurize to a preset pressure of 150MPa; then, cooled at a cooling rate of 100°C / min, and the pressure is released after cooling to below 200°C until it reaches room temperature and normal pressure, thereby obtaining a pre-sintered magnetic core;
[0039] (2) The pre-burned magnetic core is placed in the magnetic field heat treatment furnace and heated to a magnetic field heat treatment temperature of 490°C at a heating rate of 10°C / min. At this time, a magnetic field parallel to the width direction of the magnetic core is applied, and the core is kept warm for 60 minutes under a magnetic field strength of 1500Gs. The core is cooled to room temperature along with the furnace to obtain an iron-based magnetic core.
[0040] Examples 2-15 and Comparative Examples 1-7
[0041] The only difference between Examples 2-15 and Comparative Examples 1-7 and Example 1 is: in steps (1)-(2), the heating and cooling rates, force field heat treatment temperature, preset pressure, magnetic field intensity, magnetic field heat treatment temperature or holding time. See Table 1 for detailed differences.
[0042] Example 16
[0043] The difference between this embodiment 1 and the embodiment is that the alloy of this embodiment is Fe in atomic percentage. 63.5Co 5 Ni 5 Si 15.5 B 7 Cu 1 Nb 3 Amorphous strip, the amorphous strip is obtained in the same way as the amorphous strip in Example 1, and can be obtained by commercial methods or by conventional methods. The homemade methods may include the following processes: (1) component ratio; (2) master alloy smelting; (3) obtaining the corresponding amorphous strip through strip spinning and strip winding.
[0044] Table 1
[0045]
[0046]
[0047] The iron-based magnetic cores prepared in the above embodiments and comparative examples were tested for performance: the inductance L of the magnetic core was tested using a Keysight Agilent 4294A precision impedance analyzer in an applied magnetic field of 1A / m and a frequency range of 1kHz to 100kHz; the effective magnetic permeability μ e Obtained through the inductance L conversion formula:
[0048] μ e =(L×L e ) / (N 2 ×A e ),
[0049] Where, L is the core inductance, μ e is the effective magnetic permeability of the core, L e is the magnetic path length of the core, A e is the effective cross-sectional area of the core, and N is the number of coil turns (the test condition is 1 turn).
[0050] μ e Change rate % calculation method: μ e Change rate % = (μ e(1kHz) -μ e(100kHz) ) / μ e(1kHz) ×100%, μ e A rate of change less than 5% is considered constant permeability.
[0051] Table 2
[0052]
[0053]
[0054] Combined with Table 2 and Appendix Figure 4-5It can be seen from Examples 1-16 and Comparative Examples 1-7 that the present invention combines force field and magnetic field heat treatment at a specific temperature so that the iron-based magnetic core contains an amorphous phase and nano-sized grains. The iron-based magnetic core finally obtained has a low, stable or constant effective magnetic permeability at 1-100KHz, and the effective magnetic permeability is in the range of 15000-35000.
[0055] Under the force field heat treatment, on the one hand, the pressure promotes the precipitation of nano-crystals but at the same time inhibits the rapid growth of nano-crystals. To a certain extent, the magnetic core is kept at a relatively low magnetic permeability and a relatively stable magnetic permeability by controlling the grain size. On the other hand, the existence of the pressure field can induce magnetic anisotropy inside the magnetic core, increase the domain wall energy, and the high domain wall energy prevents the movement of the domain wall. To a certain extent, the magnetic permeability of the magnetic core is relatively low and the magnetic permeability is relatively stable by regulating the domain wall energy. Figure 2 As shown. The actual effect of magnetic field heat treatment is to induce grain orientation growth, that is, to promote the orientation of nano-grains along the direction of magnetic field application, thereby inducing magnetic anisotropy and regulating the shape of hysteresis loop. Force field heat treatment and magnetic field heat treatment are mutually coordinated. It is necessary to regulate the grain and domain wall energy by force field heat treatment, and then regulate the induced grain orientation growth by magnetic field heat treatment. The present invention regulates the grain size, state, magnetic anisotropy, hysteresis loop shape, etc. by changing the heat treatment process to obtain a magnetic core with stable magnetic permeability at 1-100KHz.
[0056] From Examples 1-15 and Comparative Examples 1-7, it can be seen that the amorphous magnetic core needs to be subjected to force field heat treatment and magnetic field heat treatment in sequence, and the temperature of the force field heat treatment and magnetic field heat treatment is a key factor affecting the magnetic permeability and stability of the magnetic core, indicating that the heat treatment temperature has a large influence on the grain size, state, anisotropy, etc. in the magnetic core. When the temperature of the force field heat treatment and the magnetic field heat treatment is 530-650°C and 435-550°C, respectively, the magnetic permeability of the magnetic core maintains high stability at 1-100KHz, and slightly deviates from the above two heat treatment temperature ranges, which may be because it will cause abnormal growth of grains, resulting in a significant increase in the rate of change of magnetic permeability, and the effect of maintaining stable or constant magnetic permeability cannot be achieved.
[0057] In Examples 2, 1, and 3, the heating rate gradually increases, and the magnetic permeability and its rate of change gradually decrease; in Examples 4, 1, and 5, the thermal field temperature gradually increases, and the magnetic permeability and its rate of change gradually increase; in Examples 6, 1, and 7, the thermal field pressure gradually increases, and the magnetic permeability and its rate of change gradually decrease; in Examples 8, 1, and 9, the cooling rate gradually increases, and the magnetic permeability and its rate of change gradually decrease. It can be observed from Examples 1-9 that in force field heat treatment, in addition to the temperature of heat treatment, the heating rate, cooling rate, and pressure all have a certain influence on the magnetic permeability and its rate of change of the magnetic core. The magnetic cores prepared in Examples 1-9 can maintain a magnetic permeability within the range of 15000-35000, and the rate of change of magnetic permeability at 1-100KHz is less than 5%, and even some of the rates of change of magnetic permeability are maintained below 3%. In addition, during the force field heat treatment process, the heating process can be achieved by simply setting the corresponding program on the furnace body, and the cooling process requires auxiliary quenching equipment to achieve a cooling rate of up to 500℃ / min.
[0058] In Examples 10, 1, and 11, the magnetic field intensity of the magnetic field heat treatment gradually increases, the magnetic permeability changes little, and the magnetic permeability change first increases and then decreases; in Examples 12, 1, and 13, the temperature of the magnetic field heat treatment gradually increases, the magnetic permeability gradually decreases, and the magnetic permeability change first increases and then decreases; in Examples 14, 1, and 15, the time of the magnetic field heat treatment gradually increases, the magnetic permeability first decreases and then increases, and the corresponding magnetic permeability change first increases and then decreases. It can be observed from Examples 1, 10-15 that the magnetic field intensity of the magnetic field heat treatment in 800-3000Gs has little effect on the magnitude of the magnetic permeability, but has a relatively large effect on the rate of change of the magnetic permeability at 1-100KHz; the high temperature and long time of the magnetic field heat treatment will cause the grain size in the magnetic core to be larger, although it can maintain a higher magnetic permeability stability, but it will significantly increase the magnetic permeability of the magnetic core. Therefore, when the temperature of the magnetic field heat treatment is 530-650℃ and the time is 20-120min, the magnetic permeability and stability of the magnetic core are more in line with the requirements.
[0059] The compositions of the amorphous strips in Examples 1 and 16 are different. Similar to Example 1, the rate of change of magnetic permeability of the magnetic core of Example 16 can be maintained at <5% at 1-100KHz, achieving better magnetic permeability stability. This shows that the method of the present invention can be suitable for alloys of different composition types.
[0060] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing an iron-based magnetic core, characterized in that: The steps include: (1) heating the iron-based amorphous magnetic core to a preset temperature and pressurizing it to a preset pressure, and then cooling it to below 200° C. and releasing the pressure to obtain a pre-burned magnetic core; the preset temperature is 530-650° C., and the preset pressure is greater than atmospheric pressure; (2) The pre-burned magnetic core is subjected to a magnetic field heat treatment, and after cooling, an iron-based magnetic core is obtained, wherein the temperature of the magnetic field heat treatment is 435-550°C.
2. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (1), the preset pressure is 100-200 MPa.
3. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (1), the heating rate when the iron-based amorphous magnetic core is heated to a preset temperature is 5-30°C / min.
4. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (1), the cooling rate is 50-1000°C / min; the pressurization method includes at least one of gas pressure pressurization and mold extrusion pressurization.
5. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: In step (2), the magnetic field intensity of the magnetic field heat treatment is 800-3000Gs, the time of the magnetic field heat treatment is 20-120min, and the cooling is natural cooling.
6. The method for preparing the iron-based magnetic core according to claim 1, characterized in that: The iron-based amorphous magnetic core described in step (1) is formed by winding an iron-based amorphous strip, and the magnetic field direction of the magnetic field heat treatment described in step (2) is parallel to the width direction of the iron-based amorphous strip.
7. The method for preparing an iron-based magnetic core according to claim 1, characterized in that: In step (1), the iron-based amorphous magnetic core comprises the following elements in atomic percentage: Fe 60-80%, Si 10-20%, B 0-10%, Cu 0-3%, Nb 0-5%, Ni 0-15%, Co 0-10%, Mo 0-10%, V 0-10%.
8. An iron-based magnetic core obtained by the method for preparing an iron-based magnetic core according to any one of claims 1 to 7.
9. The iron-based magnetic core according to claim 8, characterized in that: The magnetic permeability of the iron-based magnetic core is constant at a frequency of 1-100kHz, and the magnetic permeability of the iron-based magnetic core is 15000-35000; the iron-based magnetic core contains an amorphous phase and nano-sized grains.
10. Use of the iron-based magnetic core according to claim 8 or 9 in the preparation of inductors and high-current power devices.
Citation Information
Cited By
Preparation method of nanocrystalline magnetic core
CN120261157A
A method for preparing nanocrystalline magnetic core
CN120261157B